Qualitative Disclosure and Changes in Sell‐Side Financial Analysts' Information Environment - Bozanic, Zahn; Thevenot, Maya (Contemporary Accounting Research, 2015)
Abstract We examine a routine and timely disclosure, earnings press releases, to determine the extent to which several novel qualitative elements of such disclosures are associated with changes in sell‐side financial analysts' information environment. Using a comprehensive set of GARCH‐based (generalized autoregressive conditional heteroscedasticity) proxies, we examine how disclosure readability's components, across‐document textual similarity, and within‐document lexical diversity alter analysts' information environment. We find that readability in the form of shorter sentences, textual similarity, and lexical diversity are strongly related to decreases in analysts' uncertainty. Further, shorter sentences and lexical diversity improve both public and private information precision, whereas similarity affects solely analysts' private information precision. While the GARCH ‐based proxies allow us to alleviate concerns regarding potentially spurious inferences (Sheng and Thevenot 2012), we note as a caveat that such an estimation restricts our inferences to large, stable, and heavily followed firms. These findings should be of interest to analysts who may wish to explore the latent information contained within the qualitative elements of disclosure, regulators who direct the form and content of disclosure, and academics who study the use (and possible misuse) of various forms of information and its presentation.